Can charcoal hemoperfusion treatment be an option for pediatric MIS-C patients? A single-center experience in a tertiary pediatric intensive care unit - ALTAŞ, ZEYNEP MEVA (My University, 2022)
Introduction Multisystem inflammatory syndrome in children (MIS-C) is a hyper-inflammatory disorder that develops following SARS-CoV-2 infection and has clinical signs that overlap with Kawasaki disease. Immunomodulatory treatments can be used in these patients. One of the alternative treatments reported in the literature is hemoperfusion therapy. In this study, we aim to evaluate our experience of charcoal hemoperfusion therapy in children admitted and followed up with a diagnosis of MIS-C at our Pediatric Intensive Care Unit (PICU). Material and Methods We performed a retrospective evaluation of children diagnosed with MIS-C and children treated with charcoal hemoperfusion who are admitted to our PICU. Results Among 49 MIS-C patients, hemoperfusion therapy was performed on 14 patients. Duration of hospitalization, duration of invasive/non-invasive ventilation, VIS, OFI, PRISM 3 scores, and mortality rates were significantly higher in the charcoal hemoperfusion group before treatment. In patients who did not respond to conventional therapies, we observed a statistically significant decrease in the need for inotrope and invasive mechanical ventilation support and statistically significant improvements in clinical indicators after hemoperfusion therapy. Discussion In our study, we observed a significant clinical and laboratory improvement by charcoal hemoperfusion in our MIS-C patients who had a severe clinical course and multiple organ failure. Conclusion In our opinion, this study is the first report regarding the use of charcoal hemoperfusion therapy in MIS-C patients, and the choice of charcoal hemoperfusion as an initial or rescue therapy is needed to be investigated in large patient groups both in children and adults who are diagnosed with COVID-19 and MIS-C.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Health Sciences; HEMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); HEMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); charcoal hemoperfusion; MIS-C; pediatric intensive care